REALISASI TERKENDALI DAN TERAMATI CONTROLLABLE AND OBSERVABLE REALIZATION - , NANDAN DWI ASTUTI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The problem of realization is used to find out the linear systems containing the known G transfer function. This final project describes the relationship between the invariant subspace with controllable subspace and the observable subspace of a linear system. Realization of the transfer function G will be controlled if the controllabe subspace of the system is invariant subspace of an operator on the state space system. Realization of the transfer function G will be observable if the observable subspace of the system is co-invariant to an operator of the state space system.